Scientific communication: students’ proficiency for workplace readiness - Bunchasansiri, Orapan; Tanprasert, Krittika; Jirachai, Peangpen (Institute of Advanced Engineering and Science, 2024)
Under the theme of “scientific communication proficiency for workplace readiness,” researchers conducted this mixed-method study to specify key elements that improve student’s proficiency for scientific communication and enhance the communicative competence in science, technology, engineering, and mathematics (STEM) for the students. Data were collected using questionnaires, in-depth interviews, and focus group discussion. The respondents and informants consisted of 351 STEM students, six STEM business executives, and three communication experts. The conceptual framework was designed based on a communicative competence model to identify relationship between skills, knowledge, and training history. The science communication model of existing core elements (CE) based on sender, message, channel, and receiver (SMCR) communication model was developed. The implication of the finding significantly escalates the practice of scientific communication. The study highlights the importance of considering different elements under SMCR in enhancing communication skills among STEM students. The expectations of business executives and communication experts’ views and feedback provided empirical inferences that significantly support the outcomes in terms of the practical implication phase. Based on the findings, the science communication model with key elements for work readiness is redesigned as the final outcome. The results could imply to enhance communication skills in various industries.